Genomic surveillance urgently needed to control wheat blast pandemic spreading across continents. - Johanna Rhodes (PLoS Biology, 2023)
A new study in PLOS Biology highlights the alarming potential of a pandemic clone of wheat blast disease to evolve fungicide-insensitive variants and argues the urgent need for genomic surveillance and preemptive breeding of resistant wheat.